AMoPCE in Higher Education Programming: a Teaching Perspective - Grotta, Alexandre; Prado, Edmir Parada Vasques (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2020: Companion Proceedings of the 16th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi.2020.13146, 2020)
Computer programming is a fundamental topic in System Analysis and related higher education courses. Given this context, the agile project-based leaning (APjBL) is a relevant teaching method. Thus, the general objective of this research is to report the application of an APjBL method, the Agile Model for Projects in Computing Education (AMoPCE) in the Brazilian context. As a result of this research, we present the adapted version of AMoPCE and its feasibility to be applied.